Peran Guru Madrasah Ibtidaiyah Sebagai Fasilitator Pembelajaran Kreativitas Siswa Di Era Digital - Aftarina, Aftarina; Afriantoni, Afriantoni; Sari, Bulan Permata; Elsi, Elsi; Restu, Restu (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the role of educators as facilitators in developing students' creativity at Madrasah Ibtidaiyah. In the digital era, educators no longer merely function as knowledge transmitters, but as mentors and companions in the process of actualizing students' potential. The method applied is a literature review through the analysis of various relevant sources concerning educators' strategies in facilitating creativity. The findings reveal that educators who act as facilitators must be able to identify the diversity of students' characteristics, implement innovative learning approaches, and utilize appropriate media to encourage active participation and critical thinking. The conclusion of this study emphasizes that the role of educators as facilitators is crucial in preparing students to become independent, innovative, and adaptive individuals in facing future challenges. Implicitly, educators need to continuously.